Exploring the relationship between mental health-related problems and undergraduate student dropout: A case study within a civil engineering program - Del Savio, Alexandre Almeida (2022)
Dropout has always been a concerning issue within higher education. This research explores the relationship between mental health-related problems and undergraduate students’ dropout rates amid the COVID-19 pandemic and within a civil engineering program. The study is quantitative descriptive, with a non-experimental and longitudinal design. Results show that the dropout rates of civil engineering students from a private university have increased, comparing before and after the COVID-19 pandemic, primarily due to mental health-related problems. Three strong tendencies within these rates have been detected, directly related to the COVID-19 pandemic. It was concluded that undergraduate students’ mental health had been undermined due to the pandemics, which has had an immediate impact on the increase of dropout rates.